Hubungan Sikap dan Pengetahuan Dengan Perilaku Hidup Bersih dan Sehat Masyarakat Komplek Villa Sukarame di Kelurahan Sukajaya Sukarame Palembang - Novianti, Leni (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In essence, a clean and healthy lifestyle is basic for preventing humans from varios disease.This study aims to determine the relationship between atitude and knowledge with healthy living behavior in the community of komp. Villa sukarame sukajaya sukarame district, palembang.Research is an analytic survey with a cross sectional approach.Population was 92 households.The Analysis was obtained  unvariate analysis and bivariate analysis with the correlation in two used was chi square ( a= 0,05) to see relationship between the independent and dependent Variable. The results of variabel attide of chi square test 0,031 and knowledge of chi square 0,011.All 0f them a meaningful relation ship to clean and healthy living behavior in the community of komp. Villa sukarame sukajaya district palembang.